2013
DOI: 10.3390/biology2031054
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Neisseria Adhesins

Abstract: Members of the genus Neisseria include pathogens causing important human diseases such as meningitis, septicaemia, gonorrhoea and pelvic inflammatory disease syndrome. Neisseriae are found on the exposed epithelia of the upper respiratory tract and the urogenital tract. Colonisation of these exposed epithelia is dependent on a repertoire of diverse bacterial molecules, extending not only from the surface of the bacteria but also found within the outer membrane. During invasive disease, pathogenic Neisseriae al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 384 publications
(435 reference statements)
0
45
0
2
Order By: Relevance
“…We chose this phenotypic approach because it has the potential to reveal active compounds while remaining agnostic on the potential targets involved in bacterial adhesion. Converging with previous studies identifying the role of meningococcal Tfp in the interaction with endothelial cells (11,13), we discovered compounds that inhibit type IV pili assembly. Because of the importance of this virulence factor in vivo (13), these compounds represent attractive candidates for adjuvant therapy in combination with existing antibiotics.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We chose this phenotypic approach because it has the potential to reveal active compounds while remaining agnostic on the potential targets involved in bacterial adhesion. Converging with previous studies identifying the role of meningococcal Tfp in the interaction with endothelial cells (11,13), we discovered compounds that inhibit type IV pili assembly. Because of the importance of this virulence factor in vivo (13), these compounds represent attractive candidates for adjuvant therapy in combination with existing antibiotics.…”
Section: Discussionmentioning
confidence: 82%
“…Central virulent properties of N. meningitidis include adhesion to host cells (11), and this constitutes an original and attractive target for treatments. Adhesion of N. meningitidis to human cells is a key step in the life cycle of this organism by allowing nasopharynx colonization and adhesion to endothelial cells, each of these events promoting blood and brain colonization by the bacteria.…”
mentioning
confidence: 99%
“…Some of the mutations upstream of porA and opc are in phase variable homopolymeric tracts, which are discussed more fully in the section below. The other mutations are upstream of the adhesins hsf /NMB0992 and NMB1994, which are involved in colonisation [53] and immune interaction during invasion [54], and frpB /NMB1988 which is a surface antigen involved in iron uptake [55]. Differential expression of these genes may be an important factor affecting invasion, but the mutations we observed that may affect this do not appear to be specific to blood or CSF.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this conclusion, increases in liver injury indicators, serum inflammatory cytokines, or disorders of tryptophan metabolism are positively associated with enrichments of the above opportunistic pathogens in PBC patients, such as the intensive association of Klebsiella bacteria with IL‐2RA, GRO‐α and MIF; Megasphaera micronuciformis with IL‐18; Anaeroglobus geminatus with the Mayo risk score; Enterobacter asburiae with IL‐18 and SCF; Paraprevotella clara with total protein and globulin; and the Neisseriaceae bacteria and Klebsiella bacteria with urinary indoleacrylate. As reported, Actinobacillus pleuropneumoniae is a major cause of respiratory disease in pigs (Klinkenberg et al ., ); Enterobacter asburiae is an opportunistic pathogen related to community‐acquired pneumonia, soft tissue infections and wound infection (Mardaneh and Soltan Dallal, ); ankylosing spondylitis and Crohn's disease are likely caused by subclinical bowel infections with Klebsiella microbes (Rashid and Ebringer, ; Sung et al ., ); and several members of Neisseria are pathogens that cause important diseases (Hung and Christodoulides, ).…”
Section: Discussionmentioning
confidence: 99%